Phytoremediation of heavy metals and PAHs at slag fill site: three-year field-scale investigation. Issue 1 (2nd January 2019) - Reddy, Krishna R.; Amaya-Santos, Gema; Yargicoglu, Erin; Cooper, Daniel E.; Negri, M. Cristina
Abstract: Big Marsh is a 121-hectares site, representative of many other sites in the Calumet region (near Chicago, IL, USA), which has been significantly altered by the steel industry and decades of legal and illegal dumping and industrial filling. The slag-containing soil at the site has been found to be contaminated with polycyclic aromatic hydrocarbons (PAHs) and heavy metals. Due to the large size of the site to be remedied, and variable distribution of the contaminants throughout the shallow depth at slightly above the risk-based levels, phytoremediation is considered as a green and sustainable remedial option. The objective of this work was to investigate the use of phytoremediation in a three-year field-scale study, specifically determine plant survival and the fate of PAHs and heavy metals in soil and plant roots and stems. Replicate test plots were prepared by laying a thin layer of compost at the ground surface and then tilling and homogenizing the slag–soil fill to a depth of approximately 0.3 m. Nine native and restoration plant species were selected and planted at the site, and their survival and growth were monitored and fate of contaminants in soil and plants were also monitored for three growing seasons. Sequential extraction procedure was performed to determine the fractionation of the heavy metals in soils before and after planting. The results showed a decrease in PAHs concentrations in the soil, probably due to enhanced biodegradation within rhizosphere. No significant decrease in heavy metal concentrations in soil was found, but they were found to be immobilized. Contaminant concentrations were found below detection limits in the plant roots and shoots samples, demonstrating insignificant uptake by the plants. Overall, selected native grasses in combination with compost amendment to the soil proved to be able to survive under the harsh site slag fill conditions, helping to degrade or immobilize the contaminants and reducing the risk of the contaminants to public and the environment.